Redes transnacionales y etnicidad: análisis sociometrico de las redes personales de latinoamericanos y africanos en Barcelona, España - Ávila Molero, Javier (2019)
Immigrant networks are increasingly complex. Today they have become multiethnic and transnational. These networks provide the framework on which immigrants develop their socialization processes and ethnic identification. This new complexity requires the development of new methodologies and concepts for analysis beyond qualitative data and metaphors, to more objective and sociometric data. How to study networks of immigrants in this new complexity? How to identify the processes and dynamics of change? In this paper we propose to use the networks as sociometric analysis tool beyond prevailing hermeneutic uses, and develop new variables for the study of "ethnicity practice" developed by immigrants in transnational space. The survey results are based on two research projects developed with groups of American and African immigrants in Barcelona, Spain, by the Laboratory of Personal Networks and Communities Department of Anthropology at the Autonomous University of Barcelona - UAB.